Pengaruh Pelatihan dan Pengalaman Kerja terhadap Kinerja Karyawan PT. Yi Shen Industrial - Ahmad Gunawan (Business Management Analysis Journal (BMAJ), 2020)
This research aims to determine the influence of training and work experience on the employee performance of PT. Yi Shen Industrial. This study used a sample of 76 respondents, data collection using questionnaire method and tested with computerized data analysis method SPSS. The research uses validity test data analysis, reusability test, classical assumption test, double linear regression analysis and hypothesis test i.e. T test to test and compare T value with T table or by looking at the value of significance. While F test to test when independent variables are simultaneously have significant or insignificant influence with the dependent variables. T Test for the training (X1) obtained t value = 25,913 with a significant value of (25,913 bigger than 1,993) and for work experience variables (X2) acquired T value = 3,622 with a significant value of (3,622 bigger than 1,993). Therefore, Ho is rejected so that Ha is significant. Training and work experience are individually influence the employee's performance is accepted in this research. F Test hypothesis testing simultaneously gained f value = 484,220 with a significant value of (484,220 bigger than 3.12). Therefore, Ho was rejected. So it can be concluded that the training variables (X1) and work experience (X2) simultaneously significantly influence the employee performance variable (Y).